2011
DOI: 10.5269/bspm.v31i1.15106
|View full text |Cite
|
Sign up to set email alerts
|

On Mannheim curves in Riemann-Otsuki space

Abstract: In this paper, we studied the Mannheim partner curves and their new characterizations are also obtained in Riemann-Otsuki space R − O 3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Yıldırım and Bektaş gave the general properties of Bertrand curves and their characterizations in Riemann-Otsuki space in [21] . Later, in [11], Küçükarslan and Yıldırım studied the Mannheim partner curves in Riemann-Otsuki space and obtained some new characterizations for this curve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yıldırım and Bektaş gave the general properties of Bertrand curves and their characterizations in Riemann-Otsuki space in [21] . Later, in [11], Küçükarslan and Yıldırım studied the Mannheim partner curves in Riemann-Otsuki space and obtained some new characterizations for this curve.…”
Section: Introductionmentioning
confidence: 99%
“…Later, in [11], Küçükarslan and Yıldırım studied the Mannheim partner curves in Riemann-Otsuki space and obtained some new characterizations for this curve.…”
Section: Introductionmentioning
confidence: 99%
“…Frenet frames are a centrical structure in modern differential geometry, in which construction is explained with regards to an object of interest rather than with regards to exterior coordinate systems. Many studies on curves using frenet frames have been reported by many mathematicians [6,7,[9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%